Resonant two-photon ionization of helium atoms studied by attosecond interferometry - Neoričić, L.; Busto, D.; Laurell, H.; Weissenbilder, R.; Ammitzböll, M.; Luo, S.; Peschel, J.; Wikmark, H.; Lahl, J.; Maclot, S.; Squibb, R. J.; Zhong, S.; et al. (Frontiers in Physics, 2022)
We study resonant two-photon ionization of helium atoms via the 1s3p, 1s4p and 1s5p 1P1 states using the 15th harmonic of a titanium-sapphire laser for the excitation and a weak fraction of the laser field for the ionization. The phase of the photoelectron wavepackets is measured by an attosecond interferometric technique, using the 17th harmonic. We perform experiments with angular resolution using a velocity map imaging spectrometer and with high energy resolution using a magnetic bottle electron spectrometer. Our results are compared to calculations using the two-photon random phase approximation with exchange to account for electron correlation effects. We give an interpretation for the multiple pi rad phase jumps observed, both at and away from resonance, as well as their dependence on the emission angle.